EXPERIMENTAL STUDY ON CI ENGINE PERFORMANCE USING BIO DIESEL BLENDS - Ramana, P.V.; Balaram, C.; SharatKumar, A.; Reddy, P.Ramanath (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Internal combustions engines are using petroleum products as a fuel for its running. Due to urbanization and increased population usage of no. of automobiles increased and consumption of petroleum products increased so continuous demand for the energy consumption increased from year to year as a result reserves of petroleum product are depleting in a faster rate. If this trend continuous in the same way entire world may face problem with shortage of petroleum products. Therefore it is necessary to find alternative fuels to be used in the standard internal combustion engine to bridge this gap of increased consumption. Simultaneously it is necessary to improve the combustion engine in terms of fuel efficiency and emissions. As we know so far petroleum based fuels are giving higher efficiency as compared with alternative fuels so to reduce the fuel consumption strict measures to be adopted to control the consumption and also alternative fuels to be developed to mix with the petroleum fuels so that petroleum product reserves will go for longer period and it will meet with increased demand. Otherwise once these fossil fuels are consumed means again it won’t exist in nature because of its non renewable nature. So in this paper focus is given to increase the existence of non renewable fuels by reducing its consumption with addition of suitable proportions of bio-fuels. In that context importance is given one is to improve the technology to increase the kilometers per hour of unit fuel consumption by improving the suitable modifications in the engine design and other is reducing the fuel consumption by adding renewable blends so petroleum products may last for several years. Here an experimental attempt is being made to reduce the consumption of fossil fuels (petroleum products) by adding bio-diesel blends of small quantities of renewable fuels. It will help to reduce the consumption of petroleum products hence longer period of reserves may be achieved. More over biodiesels are bio degradable, eco-friendly, on toxic and clean burning In this experimentation an attempt to mix the cotton seed oil of different proportions with diesel on a single cylinder diesel engine conducted and various performances are studied in keeping view of reduce the consumption quantity and environmental safety by controlling the exhaust emissions Bio-diesel has gained much attention in recent years due to the increasing environmental awareness. It is produced from renewable resources and, more importantly, is a clean burning fuel that does not contribute to the net increase of carbon dioxide.